INCORPORATING CULTURE INTO FOREIGN LANGUAGE CURRICULUM AND MATERIALS - Effendi Gultom (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2016)
INCORPORATING CULTURE INTO FOREIGN LANGUAGE CURRICULUM AND MATERIALS Effendy Gultom Department of English Language Teaching, Riau University, Pekanbaru, Indonesia effendygultom@gmail.com Abstract: Language is a part of culture. Therefore, it is important to incorporate culture into language teaching in general and into foreign language teaching in particular. Consequently, we need to incorporate culture into foreign language curriculum and materials. In Indonesia, English is taught as a foreign language because it is not used in daily communication. However, in reality we observe that many students in Indonesia do not understand the English culture although they learn the language. For example, we often hear students asking questions that are not culturally acceptable in English context such as asking about a woman’s age, asking about someone’s salary, and asking about the prices of someone’s clothes and shoes. Many other expressions are not suitable for the occasions where they are used. This condition is probably caused by the curriculum and materials that have not incorporated English culture into the English language teaching. English teachers need to have adequate knowledge concerning with English culture if they want to be successful in their teaching. They should acquaint themselves with the specific customs and habits of the English people and they should try to be sympathetic to English culture as well. Knowledge about English culture is particularly needed when people want to visit England, Australia, New Zealand, and the United States of America. Without having knowledge about English culture, people will probably experience some culture shock when they visit those countries. Keywords: incorporating, culture, curriculum